Association between sexual harassment or violence in the work or school environment and signs of burnout among women in Iceland - Gylfi Hvannberg 1992- (2020)
Background: Prior studies have indicated that sexual harassment and violence in the workplace and at school can have a traumatic effect and may lead to burnout. Signs of burnout are for example experiencing exhaustion and frequent long-term sick absences from work. This cross-sectional study aimed to explore the association between sexual harassment or violence in the current work- or school environment and signs of burnout among women in Iceland. Methods: The participants in this study were 12022 women with a mean age of 46 years (standard deviation 15 years), who participated in the SAGA cohort in 2018. The SAGA study is population-based and had exclusively women who speak Icelandic and were at the age of 18 or older. In the study, participants answered an electronic questionnaire. Two questions in the SAGA cohort were used for signs of burnout, the first was if participants experienced exhaustion in the past seven days and the second how often they had in the past 12 months taken a long-term sickness absence, for 15 days or longer. One question was used to assess the exposure and asked whether the participants have experienced sexual harassment or violence in their workplace or school environment. Results: In the present study, 10% of the participants reported sexual harassment or violence in their current workplace or school environment. Experiencing sexual harassment or violence in the current workplace or school environment was associated with experiencing exhaustion in the past 7 days (OR=1.44; 95% CI: 1.21-1.72) compared with not experiencing sexual harassment or violence. Experiencing sexual harassment or violence in the current workplace or school environment was also associated with frequent long-term sick absence, twice or more in the past 12 months, compared with not experiencing sexual harassment or violence (OR=1.62; 95% CI: 1.03-2.56). Conclusion: One in every ten women reported experiencing sexual harassment or violence in their current workplace or school environment. The present study found an ...